THE VALUE RELEVANCE OF INTERNATIONAL ACCOUNTING STANDARD IMPLEMENTATION AND AUDIT QUALITY - Zulhaimi, Hanifa; R. Nelly Nur Apandi, R. Nelly (Jurnal Riset Akuntansi dan Keuangan, 2015)
The implementation of international accounting standards in Indonesia has significantly affected financial reporting. It increases information relevance for the investors because a fair value comprehensively represents assets and liabilities of an entity as of the balance sheet date. However, this triggers polemics over the value relevance of International Financial Reporting Standard (IFRS). This can be seen from stock price decline. This study aims to find out the effect of net income and other comprehensive income on stock price and to observe the effect of other comprehensive income moderated by audit quality. Furthermore this study also aims to find out the effect ofÂ  the subjectivity of OCI components. Using a sample of 79 companies, the writer analyzes 2014 financial statements derived from Indonesia Stock Exchange. Based on the result, the predetermined hypotheses are unable to prove. Net income is the only variable that affects stock return. Thus it can be concluded that net income has a value relevance for the investors in making economic decisions.